PENGARUH JUMLAH WISATAWAN, JUMLAH HOTEL, DAN TINGKAT HUNIAN HOTEL TERHADAP PENERIMAAN PAJAK HOTEL (STUDI KASUS PADA KOTA YOGYAKARTA) - Anggitasari Aliandi, Vidya Dwi; Handayani, Herniwati Retno (Diponegoro Journal of Economics, 2013)
A hotel tax revenue is a high potential income for Yogyakarta as a tourism city. However, this contribution to revenue tends to fluctuate. This study aims to determine the influence of the number of tourists, the number of hotels and hotel occupancy rates in Yogyakarta from 2001 to 2011 for hotel tax revenue.The analytical method used in this research is Â descriptive analysis and multiple linear regression analysis. Descriptive analysis explains the description of the data that comprises the study of the number of tourists, the number of hotels and hotel occupancy rates in Yogyakarta from 2001 to 2011. While the multiple linear regression analysis is used to prove the hypothesis of the influence of the number of tourists, the number of hotels and hotel occupancy rates for hotel tax revenue.The results showed a positive influence of tourists numbers and hotel occupancy rates for Yogyakarta hotel tax revenue. This means that the higher of the number of tourists and hotel occupancy rates, relate to the higher income of the tax revenue in Yogyakarta. The findings of the study also generate that amount of hotel is not give a positive influence on the hotel tax revenue in Yogyakarta. This means that the number of hotels will not affect the tax revenue in Yogyakarta.